2014
DOI: 10.1183/09059180.00004413
|View full text |Cite
|
Sign up to set email alerts
|

Tissue remodelling in chronic bronchial diseases: from the epithelial to mesenchymal phenotype

Abstract: Airway remodelling is a critical feature of chronic bronchial diseases, characterised by aberrant repair of the epithelium and accumulation of fibroblasts, which contribute to extracellular matrix (ECM) deposition resulting in fixed bronchial obstruction. Recently, epithelial-mesenchymal transition (EMT) has been identified as a new source of fibroblasts that could contribute to the remodelling of the airways. This phenomenon consists of the loss of the epithelial phenotype by bronchial epithelial cells and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(138 citation statements)
references
References 167 publications
1
128
0
4
Order By: Relevance
“…It was also shown that EMT could be induced in vitro in (human and rat) alveolar epithelial cells, notably by TGF-β [21]. In contrast, the occurrence and relevance of EMT in chronic airway diseases remains debated [22,23]. Findings in experimental asthma and in vitro epithelial responses to TGF-β and allergens suggested a role for EMT in allergic asthma [24], but direct evidence of constitutive overexpression of mesenchymal markers by the asthmatic bronchial epithelium is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that EMT could be induced in vitro in (human and rat) alveolar epithelial cells, notably by TGF-β [21]. In contrast, the occurrence and relevance of EMT in chronic airway diseases remains debated [22,23]. Findings in experimental asthma and in vitro epithelial responses to TGF-β and allergens suggested a role for EMT in allergic asthma [24], but direct evidence of constitutive overexpression of mesenchymal markers by the asthmatic bronchial epithelium is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly EMT has also been shown to occur in chronic obstructive pulmonary disease [41], where patients have many comparable clinical symptoms to that of CF sufferers.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This transition is characterized by reduction of their cell-to-cell contacts, the downregulation of certain markers (such as E-cadherin, claudin, or mucin-1), enhanced cell migration, and induction of mesenchymal gene expression (such as Snail 1, fibronectin, α-smooth muscle actin (α-SMA), vimentin, and cyclin D1). 90,91 Different reports suggest that EMT is linked to airway remodeling in asthma. 70,92 Interestingly, EMT is regulated by the Wnt/β-catenin and the noncanonical Wnt signaling pathway.…”
Section: Role Of Wnt Pathways In Airway Remodelingmentioning
confidence: 99%